Knowledge engineering and knowledge management : 19th International Conference, EKAW 2014, Linkoping, Sweden, November 24-28, 2014. Proceedings - Schlobach, Stefan; Lambrix, Patrick; Hyvonen, Eero; Janowicz, Krzysztof (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 19th International Conference on Knowledge Engineering and Knowledge Management, EKAW 2014, held in Linköping, Sweden, in November 2014. The 24 full papers and 21 short papers presented were carefully reviewed and selected from 138 submissions. The papers cover all aspects of eliciting, acquiring, modeling, and managing knowledge, the construction of knowledge-intensive systems and services for the Semantic Web, knowledge management, e-business, natural language processing, intelligent information integration, personal digital assistance systems, and a variety of other related topics.